Professional Competence of Islamic Jurisprudence Teachers in the Implementation of the Independent Learning Curriculum at MTs Amaliyah Sunggal - Ratih Anggraini; Muhammad Yunan (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The implementation of the Independent Learning Curriculum at MTs Amaliyah Sunggal requires an increase in the professional competence of teachers, especially in the subject of fiqh. This competence includes the ability to design and implement innovative learning, as well as utilize technology effectively. This study aims to analyze the professional competence of fiqh teachers in facing the demands of the new curriculum. The research method used is qualitative with a descriptive approach. Data collection techniques use observation, interviews, and documentation.. Data analysis techniques through the stages: data condensation, data presentation, and drawing conclusions and verification. The results of this study indicate that the form of professional competence of Islamic Jurisprudence teachers is driven by several supporting factors, such as strong and visionary support from the principal, the opportunity to participate in training, and school policies that support learning based on the Independent Curriculum. However, on the other hand, there are several obstacles, such as old habits with the previous curriculum, limited time to attend training, heavy teaching load, lack of understanding of the Independent Curriculum, and minimal knowledge of technology. Then further efforts to improve teachers' understanding of the Independent Curriculum and provide more intensive training and better access to educational technology